The Japan Society for Neuro-Oncology guideline on the diagnosis and treatment of central nervous system germ cell tumors. Issue 4 (21st October 2021) - Nakamura, Hideo; Takami, Hirokazu; Yanagisawa, Takaaki; Kumabe, Toshihiro; Fujimaki, Takamitsu; Arakawa, Yoshiki; Karasawa, Katsuyuki; Terashima, Keita; Yokoo, Hideaki; Fukuoka, Kohei; Sonoda, Yukihiko; Sakurada, Kaori; et al.
Abstract: Primary CNS germ cell tumors (GCTs) are rare neoplasms predominantly observed in the pediatric and young adult populations. In line with the hypothesis that the primordial germ cell is the cell-of-origin, histopathological examinations for this pathology involve a diverse range of components mirroring the embryogenic developmental dimensions. Chemotherapy and radiotherapy are the mainstays of treatment, with surgery having a limited role for diagnosis and debulking of residual tissue after treatment. While better management has been achieved over recent decades by modifying radiation coverage and selecting appropriate chemotherapy, standardization of treatment remains challenging, partly due to the low volume of cases encountered in each institution. As the incidence is higher in East Asia, including Japan, the Japan Society for Neuro-Oncology established a multidisciplinary task force to create an evidence-based guideline for CNS GCTs. This guideline provides recommendations for multiple dimensions of clinical management for CNS GCTs, with particular focus on diagnostic measures including serum markers, treatment algorithms including surgery, radiotherapy, and chemotherapy, and under-investigated but important areas such as treatment for recurrent cases, long-term follow-up protocols, and long-term sequelae. This guideline serves the purpose of helping healthcare professionals keep up to date with current knowledge and standards of management for patients with this rare disease in daily clinical practice, as well as driving future translational and clinical research by recognizing unmet needs concerning this tumor.